Edukasi Literasi dan Numerasi Awal Bagi Orang Tua, Guru PAUD, dan Tutor Rumah Baca di Kampung Yoboi, Kabupaten Jayapura - Diana Setyaningsih; Erna Olua; Catur F. Djarwo; Florentina M. Panda; Siti R. Ayub; Yalince Yikwa (LPPM Uncen, 2026)
The low achievement of early childhood literacy and numeracy in Indonesia, particularly in the Papua region, is an issue that requires intervention not only from formal educational institutions but also from families and the broader community. This community service activity aims to enhance the understanding of parents, early childhood education (PAUD) teachers, reading center tutors, and Sunday school caregivers regarding the concepts and methods of stimulating early literacy and numeracy in young children. The activity was conducted in the form of a seminar and workshop titled The Importance of Early Literacy and Numeracy at Rumah Baca Omomi Niphi, Yoboi Village, Jayapura Regency. The methods employed included interactive lectures, question-and-answer sessions, and group assignments to design simple educational games using locally available materials. The results of the activity indicate an improvement in participants’ understanding of the six components of early literacy, namely oral language skills, background knowledge, vocabulary, phonemic awareness, print awareness, and early writing skills. In addition, participants demonstrated increased understanding of seven aspects of early numeracy, including numbers and basic operations, geometric shapes, problem-solving, data estimation, measurement, sorting and classifying, and spatial awareness. Participants were also able to produce simple educational game products that can be directly implemented at home and in reading centers. This activity is expected to serve as a sustainable community empowerment model in supporting the development of foundational skills in early childhood, particularly in regions with limited access to education.